2007
DOI: 10.1002/hep.21751
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of human liver biopsies: Hepatitis C virus–induced fibrosis and mitochondrial dysfunction

Abstract: Liver biopsies from hepatitis C virus (HCV)-infected patients offer the unique opportunity to study human liver biology and disease in vivo. However, the low protein yields associated with these small samples present a significant challenge for proteomic analysis. In this study we describe the application of an ultrasensitive proteomics platform for performing robust quantitative proteomic studies on microgram amounts of HCV-infected human liver tissue from 15 patients at different stages of fibrosis. A high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 124 publications
4
98
0
Order By: Relevance
“…Mitochondria were purified using Nycodenz (Nycomed Pharma, Zürich, Switzerland) according to the protocols reported by Okado-Matsumoto et al 17 For transient transfection experiments, HepG2 cells were transfected with a core-expression plasmid using TransIT-LT1 (Mirus Bio, Madison, WI). Huh7 cells harboring HCV genotype 1b full-genomic (RCYM1) 18 or subgenomic replicon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and livers of 3-month-old core-gene transgenic mice 2 were also used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria were purified using Nycodenz (Nycomed Pharma, Zürich, Switzerland) according to the protocols reported by Okado-Matsumoto et al 17 For transient transfection experiments, HepG2 cells were transfected with a core-expression plasmid using TransIT-LT1 (Mirus Bio, Madison, WI). Huh7 cells harboring HCV genotype 1b full-genomic (RCYM1) 18 or subgenomic replicon (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and livers of 3-month-old core-gene transgenic mice 2 were also used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9] A recent study found, by the proteomic profiling of biopsy specimens, that an impairment in key mitochondrial processes, including fatty acid oxidation and oxidative phosphorylation, and in the response to oxidative stress occurs in HCV-infected human liver with advanced fibrosis. 10 Therefore, it is probable that the HCV core protein affects mitochondrial functions because such pathogenesis is observed in both HCV core-transgenic mice and HCV-infected patients. [11][12][13] The recent progress in proteomics has opened new avenues for disease-related biomarker discovery.…”
mentioning
confidence: 99%
“…[137][138][139][140] One of the first detailed proteomics study related to HCV biology was performed by Yan et al 141 In this study, they used isotope-coded affinity tags (ICAT) to examine differentially expressed proteins during interferon treatment of Huh-7 cells. Their study identified novel IFN regulated proteins and pathways including metabolism and dynamics of microtubule function, thereby providing further insights to the possible mechanisms of antiviral effects of interferon at the protein level and a global view of the antiviral state that the host cell undertakes during interferon treatment.…”
Section: Proteomic Approachesmentioning
confidence: 99%
“…There are few studies that investigated proteomic changes in HCV-associated fibrogenesis. Diamond et al demonstrated the effect of oxidative stress proteins to fibrosis progression in biopsy samples of HCV-infected patients [76]. The same group recently analyzed proteomic mechanisms of HCV-mediated liver fibrosis in posttransplant recipients by LC-MS (liquid chromatography coupled mass spectrometry) and demonstrated once again the important role of enhanced oxidative stress in the rapid fibrosis progression observed in HCV-infected liver transplant patients [77].…”
Section: Proteomic Profiling Studies In Search Of Biomarkers For Livementioning
confidence: 99%